Identification of a New Class of Adenosine Deaminase from Helicobacter pylori with Homologs among Diverse Taxa - Miller, Erica F. (American Society for Microbiology, 2013)
Early studies of Helicobacter pylori's nutritional requirements alluded to a complete purine salvage network in this organism. Recently, this hypothesis was confirmed in two strains of H. pylori, whose purine requirements were satisfied by any single purine base or nucleoside. Most of the purine conversion enzymes in H. pylori have been studied using mutant analysis; however, the gene encoding adenosine deaminase (ADD) in H. pylori remained unidentified. Through stepwise protein purification followed by matrix-assisted laser desorption ionization–time of flight mass spectrometry (MALDI-TOF), we discovered that H. pylori ADD is encoded by hp0267, an apparently essential gene. Hp0267 shares no sequence homology with previously characterized ADDs, yet both are members of the amidohydrolase superfamily. Hp0267 is grouped within cog0402, while other ADDs studied to date are found in cog1816. The hp0267 locus was previously misannotated as encoding a chlorohydrolase. Using purified recombinant Hp0267, we determined the enzyme's pH optimum, temperature optimum, substrate specificity, and estimated kinetic constants. In contrast to other known ADDs, Hp0267 contains Fe(II) as the relevant metal ligand. Furthermore, Hp0267 exhibits very low deaminase activity on 2′-deoxyadenosine, a substrate that is readily hydrolyzed by cog1816 ADDs. Our preliminary comparative genomic analysis suggests that Hp0267 represents a second enzyme class of adenosine deaminase whose phyletic distribution among prokaryotes is broad.